Superior nanopatterns via adjustable nanoimprint lithography on aluminum oxide in high-K thin films with ultraviolet curable polymer. Issue 1 (20th December 2021) - Oh, Jin Young; Kim, Eun-Mi; Heo, Gi-Seok; Kim, Dong Hyun; Lee, DongWook; Jeong, Hae-Chang; Seo, Dae-Shik
Abstract : The present study substantiate that ultraviolet-nanoimprint lithography (UV-NIL) can be used to transfer a one-dimensional nano-pattern onto a high-k thin film of aluminum oxide mixed with a UV photocuring agent. Abstract : The present study substantiate that ultraviolet-nanoimprint lithography (UV-NIL) can be used to transfer a one-dimensional nano-pattern onto a high-k thin film of aluminum oxide mixed with a UV photocuring agent. Polydimethylsiloxane (PDMS) molds fabricated on silicon wafers were made using deep ultraviolet laser interference lithography in order to investigate one-dimension nanopatterns. These imprinted nano-patterns induce geometric deformations in the liquid crystal (LC), creating collective and elastic properties, which act as a guide for homogeneous alignment. The nanoimprint method can process a large area, so it can be processed much easier, faster, and more accurately than the conventional rubbing method. Moreover, the optical properties of the nano-imprinted aluminum oxide (AlO) thin-film are about 1.5p% superior to that of conventional commercialized cells, so it has a high effect on the luminance and color gamut of the display. After pattern imprinting, atomic force microscope (AFM) was performed to confirm the result. We can compared the cycle of AlO mixed with UV photocuring agent PDMS pattern cycle, the period is 776 and 750 nm, the width is 468 and 450 nm, the spacing is 292 and 300 nm, and the height is 40 and 30 nm. The nano-imprinted film appears to replicate the width, amplitude, and spacing of the PDMS template. In addition, X-ray photoelectron spectroscopy was performed to determine the chemical properties of the thin film and it was confirmed that UV irradiation induces oxidation, thus increases the intensity significantly. The binding energies of Al 2p and C–O spectra were situated at 74.27 ± 0.5 eV and 531.78 ± 0.5 eV, respectively.